INOVASI HIGH EARLY STRENGTH CONCRETE DENGAN PEMANFAATAN LIMBAH BATU GRANIT, CANGKANG KERANG DAN FLY ASH - Prasetya, Wahyu Hudha (Jurnal Proyek Teknik Sipil, 2019)
Environmentally friendly concrete is concrete composed of materials that do not damage the environment. The need for the use of environmentally friendly materials in the manufacture of high quality concrete that is environmentally friendly needs to be continuously developed. To realize the concept of environmentally friendly and high-quality concrete in the concrete experiment this time used granite broken waste as a partial aggregate of coarse aggregate, as well as shell and powder ash shells as a partial cement substituent. Using waste that is not appropriate and is converted into an appropriate substitute material is expected to produce high quality concrete and environmentally friendly concept, because the use of unused waste is expected to reduce the amount of waste that is around the Surakarta area. With the use of granite fragments, shells and fly ash, the compressive strength is targeted at 1 day of age is 22 MPa and 28 days is 47 MPa.The mix design method used is the SNI method (Indonesian National Standard). Mix design in the manufacture of environmentally friendly concrete refers to the use of granite broken waste as a partial substituent of coarse aggregate, the use of shell shell waste of 7.5% of the total cement weight, and the use of fly ash of 25% of the total cement weight. With FAS of 0.3%, and the use of admixture in the form of Superplasticizer of 0.6% to accelerate the achievement of quality earlier in the first week.